Signatures of the Adler–Bell–Jackiw chiral anomaly in a Weyl fermion semimetal - Cheng-Long Zhang (Nature Portfolio, 2016)
Anomalous conducting behavior of solids may reflect the presence of novel quantum states. Here, Zhang et al. report an increased conductivity in TaAs with a magnetic field applied along the direction of the current, which reveals an inherent property of the Weyl Fermion.